Korean pansori as voice theatre : history, theory, practice - Park, Chan E., 4 0 16; 5 (London ;;New York : Methuen Drama, 2023)
This book introduces readers to the historical, performative, and cultural context of pansori, a traditional Korean oral story-singing art. Written by a scholar-practitioner of the form, this study is structured in three parts and analyzes its technical, aesthetic, and theoretical components, as well as narrating its origins, historical context and subsequent development, and its preservation and reinvention from the 20th century to today. Drawing on her ethnographic work and performance practice, Chan E. Park interweaves expert knowledge of both the textual and performative aspects of the form--
Introduction. Orality of Storysinging -- Section I. Technique and Practice of Pansori. Voice, Drum, Listening Ear ; Jangdan, the heartbeats of storytelling -- Section II. Historical Development. 18th-19th century ; Negotiating Dramatic Modernization -- Section III. Beyond the Twentieth Century. Preservation and Reinvention, Mutually ; 'Singing who you are' : an autoethnography -- Conclusion.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; History and criticism.;Philosophy and aesthetics.;Performance. -- P'ansori;P'ansori;P'ansori -- 20; 20; 2